Будинок «Слово» в Харкові - Сошенко, Д. Д. (ХНУРЕ, 2020)
In the history of Ukrainian literature, there were tragic moments and one of the most striking examples is the tragic fate of writers who fought for their freedom of speech and after which many were killed. In my work, I talk about the architectural monument House Word in which many of the writers lived, in difficult times of struggle with the highest authority.
Keywords: культурне розмаїття; українознавство; традиції; культура